'Here, without English, you are dead': ideologies of language and discourses of neoliberalism in adult English language learning. Issue 5 (3rd July 2016) - Warriner, Doris S.
ABSTRACT: Ideologies of language (and language learning) – in concert with discourses of individualism and meritocracy that characterize neoliberalism – shape pedagogical policies and practices in ways that are consequential for multilingual students all over the developing and developed world. To investigate how such intersections and influences work in adult language teaching/learning settings, this paper critically examines written documents produced by an adult ESL programme, comments made by some of the teachers, and the everyday talk of advanced students in the programme. Understanding neoliberalism as 'a theory of political economic practices that proposes that human well-being can best be advanced by liberating individual entrepreneurial freedoms and skills within an institutional framework characterized by strong private property rights, free markets, and free trade' [Harvey, D. 2005. A Brief History of Neoliberalism . Oxford: Oxford University Press, 3], I examine 'the local political economy of linguistic and cultural resources' [Heller, M. 2003. "Globalization, the New Economy, and the Commodification of Language and Identity." Journal of Sociolinguistics 7 (4): 473–492, 476] in an adult ESL programme. Findings show that texts and talk alike limit the identities (and trajectories) that are imagined for adult refugee learners of English. In some cases, even well-intended and seemingly 'neutral' descriptions of pedagogical goals and priorities might become a subtle but powerful way to further the neoliberal agenda of preparing workers for minimum-wage, entry-level employment across sectors of the economy.